Floristic list of the family Poaceae of the state of Morelos, Mexico - Sánchez-Ken, J. Gabriel; Cerros-Tlatilpa, Rosa (Instituto de Ecología, A.C., 2016)
Several national and foreign herbaria were reviewed to obtain the checklist of the family Poaceae of the state of Morelos, Mexico. The family is represented by 104 genera, 306 species and 10 infraspecific categories, classified in eight subfamilies with Chloridoideae, Panicoideae and Pooideae the most diverse ones. Morelos is repositioned from the 20th to the 13th most diverse state in Mexico with respect to species richness of the family. We present a brief analysis of the knowledge of the flora in this state by municipalities, as well as the collection effort that has been made throughout the years. Seven noxious weed species, which are listed in Mexican laws are recorded in the state.